Case-tailored indicated extracapsular dissection versus “one-size-fits-all” nerve dissection: Has the bet been won? - Mantsopoulos, Konstantinos; Gehrking, Mika; Thimsen, Vivian; Sievert, Matti; Müller, Sarina Katrin; Rupp, Robin; Balk, Matthias; Gostian, Antoniu-Oreste; Koch, Michael; Iro, Heinrich (American Journal of Otolaryngology, 2024)
Objective: The aim of the study was to trace the development of surgical therapy in a large cohort, examine its changes at one single institution that has been specializing in salivary gland pathologies over the last 22 years, and to determine the extent to which a possible shift in the surgical therapy of parotid benign tumors towards less radical methods was correlated with a change in the incidence of facial palsy and Frey's syndrome. Study design: Retrospective clinical study. Methods: A retrospective evaluation of the records of all patients treated for benign parotid tumors at a tertiary referral center between 2000 and 2022 was carried out. Surgical methods were classified into four groups: extracapsular dissection, partial superficial parotidectomy, superficial parotidectomy and complete parotidectomy. Results: A total of 4037 patients were included in the study. Our analysis demonstrated an increase in the total number of parotidectomies for benign lesions from 71 (2000) to 298 (2022), mostly due to the increase in extracapsular dissections (from 9 to 212). The increased performance of less radical surgery was associated with a significantly decreased incidence of perioperative complications. Conclusions: Our study showed that the increased performance of less radical surgery was associated with better functional outcomes over the years.
CRIS-Team Scopus Importer:2024-04-19
Keywords: Extracapsular dissection; Facial nerve; Fistula; Frey's syndrome; Paresis; Parotid gland; Parotidectomy